2006
DOI: 10.1038/sj.onc.1209805
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of RUNX3 and TES by hypermethylation in glioblastoma

Abstract: Glioblastoma, the most aggressive and least treatable form of malignant glioma, is the most common human brain tumor. Although many regions of allelic loss occur in glioblastomas, relatively few tumor suppressor genes have been found mutated at such loci. To address the possibility that epigenetic alterations are an alternative means of glioblastoma gene inactivation, we coupled pharmacological manipulation of methylation with gene profiling to identify potential methylation-regulated, tumor-related genes. Dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 65 publications
8
103
0
2
Order By: Relevance
“…Prior reports have suggested that RUNX3 is frequently inactivated in human cancer cells and can be activated by hemizygous deletion of the RUNX3 gene, hypermethylation of the Runx3 promoter, or cytoplasmic sequestration of RUNX3 protein 32, 34. Furthermore, accumulating evidence demonstrated RUNX3 could inhibit the proliferation, tumourigenic and metastasis of glioma cells 21.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports have suggested that RUNX3 is frequently inactivated in human cancer cells and can be activated by hemizygous deletion of the RUNX3 gene, hypermethylation of the Runx3 promoter, or cytoplasmic sequestration of RUNX3 protein 32, 34. Furthermore, accumulating evidence demonstrated RUNX3 could inhibit the proliferation, tumourigenic and metastasis of glioma cells 21.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse tumor tissues have been reported to exhibit RUNX3 hypermethylation and inactivation. These include tissues and cell lines that originated from gastric (Li et al, 2002;Oshimo et al, 2004), bladder (Kim et al, 2005;Wolff et al, 2008), colorectal (Ahlquist et al, 2008;Soong et al, 2009;Subramaniam et al, 2009), breast (Lau et al, 2006;Jiang et al, 2008), lung (Sato et al, 2006), pancreatic (Wada et al, 2004), brain cancers (Mueller et al, 2007), and hepatocellular carcinoma . Notably, RUNX3 methylation status is one of the five markers used to classify colorectal tumors associated with very high frequencies of CpG island methylation (CIMP), microsatellite instability, and BRAF mutation (Weisenberger et al, 2006).…”
Section: Epigenetic Silencing Of Runx3mentioning
confidence: 99%
“…18 A 324 bp-fragment covering all 22 CpG sites in CpG island I, a 379 bp-fragment covering all 21 CpG sites in CpG island II, as well as a 302-bp fragment covering 19 out of 29 CpG sites in CpG island III were individually amplified by PCR from sodium bisulfite-modified DNA (for primers see Table I). The respective PCR products were cloned using One Shot Escherichia coli cells and the TOPO TA Cloning Kit (Invitrogen Life Technologies, Carlsbad, CA).…”
Section: Methylation Analysis Using Sodium Bisulfite Sequencingmentioning
confidence: 99%